Self-repairing thermoplastic elastomer containing dynamic covalent bonds, synthesis method of self-repairing thermoplastic elastomer and preparation method of interlayer toughening self-repairing electromagnetic shielding composite material

By introducing the self -repairing thermoplastic elastic body of the dynamic co -price bond in the electromagnetic shielding composite material, the problem of poor toughness and self -repairing the existing material layer has been solved, and efficient electromagnetic shielding and multiple self -repairing performance are achieved.

CN119350593APending Publication Date: 2025-01-24INST OF PETROCHEM HEILONGJIANG ACADEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411485903.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing fiber-reinforced polymer-based electromagnetic shielding composite materials have problems such as poor shielding effect, low interlayer toughness, inability to self-repair between composite materials or low repair efficiency, and inability to repetitively repair.

Method used

Self -repairing thermoplastic elastomes with dynamic covalent keys, through the formation of dynamic sulfur bonds and dynamic hydrogen bonds, design and prepare the tough self -repairing electromagnetic shielding composite materials. This material is obtained through hot -melt co -mixed, grinding dispersing, vacuum pinching, hot pressure composite, layer of cross -stacking and thermal curing process.

Benefits of technology

The excellent electromagnetic shielding performance (≥60DB) and multiple high -efficiency inter -layer self -repair performance of composite materials in the X -band (inter -layer repair efficiency ≥90%, and the number of self -repair ≥ 10 times).

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350593A_ABST
    Figure CN119350593A_ABST
Patent Text Reader

Abstract

The invention discloses a self-repairing thermoplastic elastomer containing dynamic covalent bonds, a synthesis method of the self-repairing thermoplastic elastomer and a preparation method of an interlayer toughening self-repairing electromagnetic shielding composite material, and belongs to the field of self-repairing electromagnetic shielding composite materials. The interlayer toughening self-repairing electromagnetic shielding composite material comprises epoxy resin, a curing agent, a toughening agent, a silver nanoparticle loaded graphene nanosheet, a self-repairing thermoplastic polymer non-woven fabric and a metal-plated carbon fiber non-woven fabric, the interlayer toughening self-repairing electromagnetic shielding composite material is obtained through hot melting blending, grinding dispersion, vacuum kneading, hot pressing compounding, layer-by-layer cross laying and thermocuring. The preparation method comprises the following steps: firstly, synthesizing three self-repairing thermoplastic elastomers, and designing and preparing a self-repairing thermoplastic polymer non-woven fabric; the interlayer toughening self-repairing electromagnetic shielding composite material with excellent electromagnetic shielding performance and multiple efficient interlayer self-repairing performance is prepared by controlling the structure and proportion of the self-repairing thermoplastic elastomer containing the dynamic disulfide bonds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of self-repairing electromagnetic shielding composite materials, and specifically relates to a self-repairing thermoplastic elastomer containing dynamic covalent bonds and a synthesis method thereof, and a preparation method of an interlayer toughened self-repairing electromagnetic shielding composite material. Background Art

[0002] At present, electronic information technology is developing rapidly, especially electronic equipment is developing towards miniaturization, high integration and high power. The rapid development of electronic information technology has brought convenience to life and promoted the development of society. However, with the increasing application of electronic equipment, many disadvantages have gradually emerged. When electronic equipment is running, a large amount of electromagnetic waves and electromagnetic radiation are generated. First, the electromagnetic waves emitted by various electronic equipment will interfere with each other, affecting the normal operation of highly sensitive electronic equipment, resulting in performance degradation or even failure; second, studies have shown that electromagnetic radiation will have different degrees of impact on human health and safety, and this damage has a cumulative effect; third, in the field of information security and communication, the leakage of electromagnetic signals will cause serious leakage problems. Therefore, electromagnetic shielding or electromagnetic radiation protection is very important. Electromagnetic shielding or electromagnetic radiation protection is often achieved through electromagnetic shielding materials. Metal materials and polymer-based composites with excellent conductive / magnetic properties are the main research hotspots of electromagnetic shielding matrix materials. In some complex environments, polymer-based composites have outstanding advantages, especially fiber-reinforced polymer-based composites. However, the current fiber-reinforced polymer-based electromagnetic shielding composite materials have the disadvantages of poor shielding effect, low interlayer toughness, inability to self-repair between composite layers or low repair efficiency, and non-repeatable self-repair. Summary of the invention

[0003] The purpose of the present invention is to solve the problems in the prior art of poor toughness between layers of electromagnetic shielding composite materials, low electromagnetic shielding effectiveness, inability to self-repair between composite layers or low repair efficiency, and non-repeatable self-repair, and further provide a self-repairing thermoplastic elastomer containing dynamic covalent bonds and a synthesis method thereof, and a method for preparing an interlayer toughened self-repairing electromagnetic shielding composite material.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions:

[0005] A self-healing thermoplastic elastomer containing dynamic covalent bonds, wherein the self-healing thermoplastic elastomer containing dynamic covalent bonds is a thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds, and the thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds includes a thermoplastic elastomer shown in structural formula I, structural formula II or structural formula III:

[0006]

[0007]

[0008] The value of n is 2 to 4.

[0009] Furthermore, the preparation method of the self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds shown in the structural formula I comprises the following steps: adding chloroform and bis(4-hydroxyphenyl) disulfide to a four-necked flask equipped with a stirrer, a condenser, a dropping funnel and nitrogen protection, stirring under nitrogen protection to form a uniform solution A, stirring solution A at 0°C for 20-40 minutes, dissolving isophorone diisocyanate and diphenylmethane diisocyanate in anhydrous chloroform solution, stirring under nitrogen protection to form a uniform solution B, and then adding solution B dropwise into solution A under nitrogen gas protection and stirring conditions. After the addition is completed, the temperature of the mixed solution is slowly raised to room temperature, and the reaction is stirred at room temperature for 24 to 72 hours. After the reaction is completed, methanol is added. alcohol and continue stirring for 15 to 30 minutes, remove the mixed solvent of methanol and chloroform, then add chloroform to dissolve, remove the chloroform solvent, repeat washing 3 to 5 times and then vacuum dry to obtain a self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds as shown in structural formula I, wherein in solution A, the ratio of bis(4-hydroxyphenyl) disulfide to chloroform is 0.01 mole:200 to 500 ml, in solution B, the ratio of the mixture of isophorone diisocyanate and diphenylmethane diisocyanate to chloroform is 0.01 mole:20 to 50 ml, the molar ratio of isophorone diisocyanate to diphenylmethane diisocyanate is 1:0.2 to 0.4, and the molar ratio of bis(4-hydroxyphenyl) disulfide to diisocyanate is 1:1.

[0010] Furthermore, the preparation method of the self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds shown in the structural formula II comprises the following steps: adding a mixture of 4,4'-diaminodiphenyl disulfide and alcohol hydroxyl-terminated dimethylsiloxane and chloroform to a four-necked flask equipped with a stirrer, a condenser, a dropping funnel and nitrogen protection, stirring under nitrogen protection to form a uniform solution C, stirring solution C at 0°C for 20-40 minutes, dissolving isophorone diisocyanate in anhydrous chloroform solution, stirring under nitrogen protection to form a uniform solution D, and then adding solution D dropwise to solution C under nitrogen gas protection and stirring conditions. After the addition is completed, the temperature of the mixed solution is slowly raised to room temperature, and the reaction is stirred at room temperature for 24 to 72 hours. After the reaction is completed, methanol is added and stirring is continued for 15 to 30 minutes. n, after removing the mixed solvent of methanol and chloroform, chloroform is added to dissolve, and the chloroform solvent is removed again. After repeated washing for 3 to 5 times, vacuum drying is performed to obtain a self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds as shown in structural formula II, wherein in solution C, the ratio of the mixture of 4,4'-diaminodiphenyl disulfide and alcohol hydroxyl-terminated dimethylsiloxane to chloroform is 0.01 mole:200 to 500 ml, and the molar ratio of 4,4'-diaminodiphenyl disulfide to alcohol hydroxyl-terminated dimethylsiloxane is 1:0.1 to 0.2; in solution D, the ratio of isophorone diisocyanate to chloroform is 0.01 mole:20 to 50 ml; the total molar ratio of 4,4'-diaminodiphenyl disulfide and alcohol hydroxyl-terminated dimethylsiloxane to isophorone diisocyanate is 1:1.

[0011] Furthermore, the preparation method of the self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds shown in the structural formula III comprises the following steps: adding chloroform and 4,4'-diaminodiphenyl disulfide to a four-necked flask equipped with a stirrer, a condenser, a dropping funnel and nitrogen protection, stirring under nitrogen protection to form a uniform solution E, stirring solution E at 0°C for 20-40 minutes, dissolving diphenylmethane diisocyanate in anhydrous chloroform solution, stirring under nitrogen protection to form a uniform solution F, and then adding solution F dropwise to solution E under nitrogen gas protection and stirring conditions. After the addition is completed, the temperature of the mixed solution is slowly raised to room temperature, and the reaction is stirred at room temperature. 24 to 72 hours, after the reaction is completed, methanol is added and stirring is continued for 15 to 30 minutes, after removing the mixed solvent of methanol and chloroform, chloroform is added to dissolve, and then the chloroform solvent is removed, and the washing is repeated 3 to 5 times and then vacuum dried to obtain a self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds as shown in structural formula III, wherein in solution E, the ratio of 4,4'-diaminodiphenyl disulfide to chloroform is 0.01 mole:200 to 500 ml, the ratio of diphenylmethane diisocyanate to chloroform in solution F is 0.01 mole:20 to 50 ml, and the molar ratio of 4,4'-diaminodiphenyl disulfide to diphenylmethane diisocyanate is 1:1.

[0012] Furthermore, the volume ratio of the methanol to the chloroform used in the reaction system is 1-1.2:8.

[0013] A method for preparing an interlayer toughened self-repairing electromagnetic shielding composite material, wherein the interlayer toughened self-repairing electromagnetic shielding composite material comprises epoxy resin, curing agent, toughening agent, silver nanoparticle-loaded graphene nanosheets, self-repairing thermoplastic polymer non-woven fabric, and metal-plated carbon fiber non-woven fabric. The interlayer toughened self-repairing electromagnetic shielding composite material is obtained by hot melt blending, grinding dispersion, vacuum kneading, hot pressing compounding, layer-by-layer cross-stacked and thermal curing. The self-repairing thermoplastic polymer non-woven fabric is composed of a self-repairing thermoplastic elastomer shown in structural formula I, a structural A blend of a self-healing thermoplastic elastomer represented by formula II, a self-healing thermoplastic elastomer represented by formula III, an ethylene-methacrylic acid copolymer and an ethylene-methyl methacrylate copolymer is prepared, wherein the mass ratio of the self-healing thermoplastic elastomer represented by formula I, the self-healing thermoplastic elastomer represented by formula II, the self-healing thermoplastic elastomer represented by formula III, the ethylene-methacrylic acid copolymer and the ethylene-methyl methacrylate copolymer is 20-30:80-100:5-10:50-100:30-50;

[0014] Furthermore, the self-repairing thermoplastic polymer non-woven fabric has a unit area mass of 10 g / ㎡ to 20 g / ㎡.

[0015] Furthermore, the epoxy resin includes bisphenol A epoxy resin, bisphenol F epoxy resin and TDE-85 epoxy resin, and the mass ratio is 100:50-70:30-50. The curing agent is a combination of micron-grade dicyandiamide, micron-grade 4,4-diaminophenyl sulfone and imidazole compounds. The particle sizes of the micron-grade dicyandiamide and micron-grade 4,4-diaminophenyl sulfone are both in the range of 5-10 microns. The mass ratio of the micron-grade dicyandiamide and the micron-grade 4,4-diaminophenyl sulfone is 100:20-50. The amount of the imidazole compound is 1%-5% of the total mass of the epoxy resin. The molar ratio of -NH groups to epoxy groups in the curing agent is 1:1-1.2.

[0016] Furthermore, the toughening agent comprises hydroxylated polysulfone resin, carboxyl nitrile rubber functionalized epoxy resin and polyetherimide powder, the mass ratio of which is 100:30-50:10-30, the toughening agent accounts for 5%-10% of the total mass of the epoxy resin, and the particle size of the polyetherimide powder is 10-25 microns; the particle size of the silver nanoparticles in the silver nanoparticle-loaded graphene nanosheets is 10nm-50nm, the loading amount of the silver nanoparticles is 30%-50%, and the amount of the silver nanoparticle-loaded graphene nanosheets is 3%-10% of the total mass of the epoxy resin; the unit area mass of the metal-plated carbon fiber non-woven fabric is 5g / ㎡-50g / ㎡, the plated metal is one of silver, nickel or silver-nickel alloy, and the surface resistance is 0.5-2.5Ω / sq.

[0017] Furthermore, the interlayer toughened self-repairing electromagnetic shielding composite material is obtained by hot melt blending, grinding dispersion, vacuum kneading, hot pressing compounding, layer-by-layer cross-stacked and thermal curing, and the specific steps are as follows:

[0018] (1) Preparation of hot melt blends

[0019] The hydroxylated polysulfone resin and the bisphenol A epoxy resin are uniformly mixed, melted and stirred in a hot melt reactor until the thermoplastic hydroxylated polysulfone resin is completely melted in the bisphenol A epoxy resin, and then the mixture is kept warm and stirred for 10 to 30 minutes to form a uniform and transparent hot melt blend A, wherein the temperature of the blend is maintained at 180 to 200° C.;

[0020] (2) Preparation of grinding dispersion resin

[0021] Firstly, silver nanoparticle-loaded graphene nanosheets and bisphenol F epoxy resin are ground on a three-roll mill for 3 to 5 times to obtain a dispersion resin B, and then the dispersion resin B is mixed with a curing agent and polyetherimide and ground on a three-roll mill for 3 to 5 times to obtain a ground dispersion resin C;

[0022] (3) Preparation of blended resin

[0023] The hot melt blend A is preheated to 50-80° C. in a blast drying oven, the heating temperature of the vacuum kneader is set to 40-50° C., and the preheating is performed for 3-5 hours. The preheated hot melt blend A, the grinding and dispersion resin C, the carboxyl nitrile rubber functionalized epoxy resin and the TDE-85 epoxy resin are added to the preheated vacuum kneader, and the blended resin D is obtained by vacuum kneading for 5-15 minutes; wherein, the material temperature is controlled at 50-60° C., and the vacuum degree is controlled at -0.098MPa to -0.095MPa during the kneading process;

[0024] (4) Preparation of interlayer toughened self-repairing electromagnetic shielding composite materials

[0025] The blended resin D and the metal-coated carbon fiber non-woven fabric are prepared into an electromagnetic shielding prepreg by a hot melt coater, and the content of the blended resin D is controlled at 40% to 45%. The electromagnetic shielding prepreg and the self-repairing thermoplastic polymer non-woven fabric are cross-laid together and then thermally cured to obtain an interlayer toughened self-repairing electromagnetic shielding composite material, wherein the self-repairing thermoplastic polymer non-woven fabric is between the electromagnetic shielding prepregs, the curing temperature is 120 to 180°C, the curing time is 2 to 4 hours, and the curing pressure is 0.3 to 0.6 MPa.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The present invention firstly synthesizes three self-healing thermoplastic elastomers containing dynamic disulfide bonds, and designs and prepares self-healing thermoplastic polymer non-woven fabrics. By controlling the structure and proportion of the self-healing thermoplastic elastomers containing dynamic disulfide bonds, the composition of the self-healing thermoplastic polymer non-woven fabrics, the structure and composition of the metal-plated carbon fiber non-woven fabrics, and the composition and proportion of the blended resin, an interlayer toughened self-healing electromagnetic shielding composite material with excellent electromagnetic shielding performance and multiple high-efficiency interlayer self-healing performance is prepared. The present invention designs and synthesizes a self-healing thermoplastic elastomer containing dynamic disulfide bonds, introduces the dynamic disulfide bonds into the structure of the thermoplastic elastomer, and endows the prepared self-healing thermoplastic polymer non-woven fabric with excellent self-healing performance and toughness, so that the electromagnetic shielding composite material has high interlayer toughness and intrinsic self-healing characteristics; the design uses metal-plated carbon fiber non-woven fabric to improve both the mechanical properties and the electromagnetic shielding performance of the composite material, and the metal layer is evenly plated on the carbon fiber to improve its dispersion uniformity. In addition, the design introduces silver nanoparticles loaded with graphene nanosheets into the blended resin, and utilizes the synergistic effect of silver nanoparticles and graphene nanosheets to improve the electromagnetic shielding performance of the composite material, while improving the dispersibility of silver nanoparticles in the blended resin; the above synergistic effects jointly endow the interlayer toughened self-healing electromagnetic shielding composite material of the present invention with excellent electromagnetic shielding performance and multiple high-efficiency interlayer self-healing performance. Based on the combined effect of the above-mentioned means and methods, the prepared interlayer toughened self-repairing electromagnetic shielding composite material has excellent electromagnetic shielding performance and multiple high-efficiency interlayer self-repair advantages. Its electromagnetic shielding effectiveness in the X-band is ≥60dB, the interlayer repair efficiency is ≥90%, and the number of high-efficiency interlayer self-repair times is ≥10 times. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of cross-stacking of interlayer toughened self-repairing electromagnetic shielding composite materials; wherein 1 is electromagnetic shielding prepreg and 2 is self-repairing thermoplastic polymer non-woven fabric. DETAILED DESCRIPTION

[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] A method for preparing an interlayer toughened self-repairing electromagnetic shielding composite material, wherein the interlayer toughened self-repairing electromagnetic shielding composite material comprises epoxy resin, a curing agent, a toughening agent, silver nanoparticle-loaded graphene nanosheets, a self-repairing thermoplastic polymer non-woven fabric, and a metal-plated carbon fiber non-woven fabric. The interlayer toughened self-repairing electromagnetic shielding composite material is obtained by hot-melt blending, grinding and dispersing, vacuum kneading, hot pressing compounding, layer-by-layer cross-stacking and thermal curing.

[0032] The self-healing thermoplastic polymer non-woven fabric is prepared from a blend of a self-healing thermoplastic elastomer shown in structural formula I, a self-healing thermoplastic elastomer shown in structural formula II, a self-healing thermoplastic elastomer shown in structural formula III, ethylene-methacrylic acid copolymer and ethylene-methyl methacrylate copolymer, wherein the mass ratio of the self-healing thermoplastic elastomer shown in structural formula I, the self-healing thermoplastic elastomer shown in structural formula II, the self-healing thermoplastic elastomer shown in structural formula III, ethylene-methacrylic acid copolymer and ethylene-methyl methacrylate copolymer is 20:80:5:50:30; the mass per unit area of ​​the self-healing thermoplastic polymer non-woven fabric is 10 g / m2.

[0033] Furthermore, the self-healing thermoplastic elastomer is a thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds, and the thermoplastic elastomers represented by structural formula I, structural formula II and structural formula III are as follows:

[0034]

[0035] The value of n is 2.

[0036] Furthermore, the preparation method of the self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds shown in the structural formula I comprises the following steps: adding chloroform and bis(4-hydroxyphenyl) disulfide to a four-necked flask equipped with a stirrer, a condenser, a dropping funnel and nitrogen protection, stirring under nitrogen protection to form a uniform solution A, stirring solution A at 0°C for 20 minutes, dissolving isophorone diisocyanate and diphenylmethane diisocyanate in anhydrous chloroform solution, stirring under nitrogen protection to form a uniform solution B, and then adding solution B dropwise into solution A under nitrogen gas protection and stirring conditions. After the addition is completed, the temperature of the mixed solution is slowly raised to room temperature, and the reaction is stirred at room temperature for 24 hours. The reaction result is After the mixture is dried, methanol is added and stirring is continued for 15 minutes. After removing the mixed solvent of methanol and chloroform, chloroform is added to dissolve it, and then the chloroform solvent is removed. The mixture is washed three times and then vacuum dried to obtain a self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds as shown in structural formula I, wherein in solution A, the ratio of bis(4-hydroxyphenyl) disulfide to chloroform is 0.01 mole:200 ml, in solution B, the ratio of the mixture of isophorone diisocyanate and diphenylmethane diisocyanate to chloroform is 0.01 mole:20 ml, the molar ratio of isophorone diisocyanate to diphenylmethane diisocyanate is 1:0.2, and the molar ratio of bis(4-hydroxyphenyl) disulfide to diisocyanate is 1:1.

[0037] Furthermore, the preparation method of the self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds shown in the structural formula II comprises the following steps: adding a mixture of 4,4'-diaminodiphenyl disulfide and alcohol hydroxyl-terminated dimethylsiloxane and chloroform to a four-necked flask equipped with a stirrer, a condenser, a dropping funnel and nitrogen protection, stirring under nitrogen protection to form a uniform solution C, stirring solution C at 0°C for 20 minutes, dissolving isophorone diisocyanate in anhydrous chloroform solution, stirring under nitrogen protection to form a uniform solution D, and then adding solution D dropwise to solution C under nitrogen gas protection and stirring conditions. After the addition is completed, the temperature of the mixed solution is slowly raised to room temperature, and the reaction is stirred at room temperature for 24 hours. After the reaction is completed, methanol is added and stirring is continued for 15 min, remove the mixed solvent of methanol and chloroform, then add chloroform to dissolve, remove the chloroform solvent, repeat washing 3 times and vacuum dry to obtain a self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds as shown in structural formula II, wherein in solution C, the ratio of the mixture of 4,4'-diaminodiphenyl disulfide and alcohol hydroxyl-terminated dimethylsiloxane to chloroform is 0.01 mole:200 ml, and the molar ratio of 4,4'-diaminodiphenyl disulfide to alcohol hydroxyl-terminated dimethylsiloxane is 1:0.1; in solution D, the ratio of isophorone diisocyanate to chloroform is 0.01 mole:20 ml; the total molar ratio of 4,4'-diaminodiphenyl disulfide and alcohol hydroxyl-terminated dimethylsiloxane to isophorone diisocyanate is 1:1.

[0038] Furthermore, the preparation method of the self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds shown in the structural formula III comprises the following steps: adding chloroform and 4,4'-diaminodiphenyl disulfide to a four-necked flask equipped with a stirrer, a condenser, a dropping funnel and nitrogen protection, stirring under nitrogen protection to form a uniform solution E, stirring solution E at 0°C for 20 minutes, dissolving diphenylmethane diisocyanate in anhydrous chloroform solution, stirring under nitrogen protection to form a uniform solution F, and then adding solution F dropwise to solution E under nitrogen gas protection and stirring conditions, and after the addition is completed, slowly raising the temperature of the mixed solution to room temperature, and evaporating at room temperature. The mixture was stirred at room temperature for 24 hours, and methanol was added after the reaction was completed and the stirring was continued for 15 minutes. After removing the mixed solvent of methanol and chloroform, chloroform was added to dissolve it, and the chloroform solvent was removed. The mixture was washed three times and then vacuum dried to obtain a self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds as shown in structural formula III, wherein in solution E, the ratio of 4,4'-diaminodiphenyl disulfide to chloroform was 0.01 mole:200 ml, and in solution F, the ratio of diphenylmethane diisocyanate to chloroform was 0.01 mole:20 ml, and the molar ratio of 4,4'-diaminodiphenyl disulfide to diphenylmethane diisocyanate was 1:1.

[0039] In the above steps of preparing structural formula I, structural formula II and structural formula III, the volume ratio of the methanol to the chloroform used in the reaction system is 1:8.

[0040] Furthermore, the epoxy resin includes bisphenol A epoxy resin, bisphenol F epoxy resin and TDE-85 epoxy resin in a mass ratio of 100:50:30.

[0041] Furthermore, the curing agent is a combination of micron-sized dicyandiamide, micron-sized 4,4-diaminophenyl sulfone and imidazole compounds. The particle sizes of micron-sized dicyandiamide and micron-sized 4,4-diaminophenyl sulfone are both in the range of 5 to 10 microns, and the mass ratio of micron-sized dicyandiamide to micron-sized 4,4-diaminophenyl sulfone is 100:20; the molar ratio of -NH groups to epoxy groups in the curing agent is 1:1; and the amount of the imidazole compound is 1% of the total mass of the epoxy resin.

[0042] Furthermore, the toughening agent comprises hydroxylated polysulfone resin, carboxyl nitrile rubber functionalized epoxy resin and polyetherimide powder in a mass ratio of 100:30:10, and the toughening agent accounts for 5% of the total mass of the epoxy resin. The particle size of the polyetherimide powder is 10 microns.

[0043] Furthermore, the particle size of the silver nanoparticles in the silver nanoparticle-loaded graphene nanosheets is 10nm-50nm, the loading amount of the silver nanoparticles is 30%, and the amount of the silver nanoparticle-loaded graphene nanosheets is 3% of the total mass of the epoxy resin.

[0044] Furthermore, the mass per unit area of ​​the metal-plated carbon fiber non-woven fabric is 5 g / ㎡, the plated metal is silver, and the surface resistance is 0.5 Ω / sq.

[0045] Furthermore, the interlayer toughened self-repairing electromagnetic shielding composite material is obtained by hot melt blending, grinding dispersion, vacuum kneading, hot pressing compounding, layer-by-layer cross-stacked and thermal curing, and the specific steps are as follows:

[0046] (1) Preparation of hot melt blends

[0047] The hydroxylated polysulfone resin and the bisphenol A epoxy resin are uniformly mixed, melted and stirred in a hot melt reactor until the thermoplastic hydroxylated polysulfone resin is completely melted in the bisphenol A epoxy resin, and then the mixture is kept warm and stirred for 10 minutes to form a uniform and transparent hot melt blend A. The temperature of the blend is maintained at 180°C.

[0048] (2) Preparation of grinding dispersion resin

[0049] First, silver nanoparticle-loaded graphene nanosheets and bisphenol F epoxy resin are ground three times on a three-roll mill to obtain a dispersion resin B, and then the dispersion resin B is mixed with a curing agent and polyetherimide and ground on a three-roll mill for 3 to 5 times to obtain a ground dispersion resin C.

[0050] (3) Preparation of blended resin

[0051] The hot melt blend A was preheated to 50°C in a blast drying oven, and the vacuum kneader was set to 40°C for 3 hours. The preheated hot melt blend A, grinding dispersion resin C, carboxyl nitrile rubber functionalized epoxy resin and TDE-85 epoxy resin were added to the preheated vacuum kneader and vacuum kneaded for 5 minutes to obtain blended resin D. During the kneading process, the material temperature was controlled at 50°C and the vacuum degree was controlled at -0.098MPa.

[0052] (4) Preparation of interlayer toughened self-repairing electromagnetic shielding composite materials

[0053] The blended resin D and the metal-plated carbon fiber non-woven fabric are prepared into an electromagnetic shielding prepreg by a hot melt coating machine, and the content of the blended resin D is controlled at 40%. The electromagnetic shielding prepreg 1 and the self-repairing thermoplastic polymer non-woven fabric 2 are cross-laid together and thermally cured to obtain an interlayer toughened self-repairing electromagnetic shielding composite material. Among them, the self-repairing thermoplastic polymer non-woven fabric 2 is between the electromagnetic shielding prepreg 1, the curing temperature is 120°C, the curing time is 2h, and the curing pressure is 0.3MPa.

[0054] The interlayer toughened self-repairing electromagnetic shielding composite material prepared by the above steps has the advantages of high electromagnetic shielding efficiency and multiple efficient self-repair between layers. Its electromagnetic shielding effectiveness in the X-band reaches 60dB, and the interlayer repair efficiency is 90%.

[0055] Example 2

[0056] A method for preparing an interlayer toughened self-repairing electromagnetic shielding composite material, wherein the interlayer toughened self-repairing electromagnetic shielding composite material comprises epoxy resin, a curing agent, a toughening agent, silver nanoparticle-loaded graphene nanosheets, a self-repairing thermoplastic polymer non-woven fabric, and a metal-plated carbon fiber non-woven fabric. The interlayer toughened self-repairing electromagnetic shielding composite material is obtained by hot-melt blending, grinding and dispersing, vacuum kneading, hot pressing compounding, layer-by-layer cross-stacking and thermal curing.

[0057] The self-healing thermoplastic polymer non-woven fabric is prepared from a blend of a self-healing thermoplastic elastomer shown in structural formula I, a self-healing thermoplastic elastomer shown in structural formula II, a self-healing thermoplastic elastomer shown in structural formula III, ethylene-methacrylic acid copolymer and ethylene-methyl methacrylate copolymer, wherein the mass ratio of the self-healing thermoplastic elastomer shown in structural formula I, the self-healing thermoplastic elastomer shown in structural formula II, the self-healing thermoplastic elastomer shown in structural formula III, ethylene-methacrylic acid copolymer and ethylene-methyl methacrylate copolymer is 30:100:10:100:50; the mass per unit area of ​​the self-healing thermoplastic polymer non-woven fabric is 20 g / m2.

[0058] Furthermore, the self-healing thermoplastic elastomer is a thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds, and the thermoplastic elastomers represented by structural formula I, structural formula II and structural formula III are as follows:

[0059]

[0060] The value of n is 4.

[0061] Furthermore, the preparation method of the self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds shown in the structural formula I comprises the following steps: adding chloroform and bis(4-hydroxyphenyl) disulfide to a four-necked flask equipped with a stirrer, a condenser, a dropping funnel and nitrogen protection, stirring under nitrogen protection to form a uniform solution A, stirring solution A at 0°C for 40 minutes, dissolving isophorone diisocyanate and diphenylmethane diisocyanate in anhydrous chloroform solution, stirring under nitrogen protection to form a uniform solution B, and then adding solution B dropwise into solution A under nitrogen gas protection and stirring conditions. After the addition is completed, the temperature of the mixed solution is slowly raised to room temperature, and the reaction is stirred at room temperature for 72 hours. The reaction result is After the mixture is dried, methanol is added and stirring is continued for 30 minutes. After removing the mixed solvent of methanol and chloroform, chloroform is added to dissolve it, and then the chloroform solvent is removed. The mixture is washed 5 times and then vacuum dried to obtain a self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds as shown in structural formula I, wherein in solution A, the ratio of bis(4-hydroxyphenyl) disulfide to chloroform is 0.01 mole:500 ml, in solution B, the ratio of the mixture of isophorone diisocyanate and diphenylmethane diisocyanate to chloroform is 0.01 mole:50 ml, the molar ratio of isophorone diisocyanate to diphenylmethane diisocyanate is 1:0.4, and the molar ratio of bis(4-hydroxyphenyl) disulfide to diisocyanate is 1:1.

[0062] Furthermore, the preparation method of the self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds shown in the structural formula II comprises the following steps: adding a mixture of 4,4'-diaminodiphenyl disulfide and alcohol hydroxyl-terminated dimethylsiloxane and chloroform to a four-necked flask equipped with a stirrer, a condenser, a dropping funnel and nitrogen protection, stirring under nitrogen protection to form a uniform solution C, stirring solution C at 0°C for 40 minutes, dissolving isophorone diisocyanate in anhydrous chloroform solution, stirring under nitrogen protection to form a uniform solution D, and then adding solution D dropwise to solution C under nitrogen gas protection and stirring conditions. After the addition is completed, the temperature of the mixed solution is slowly raised to room temperature, and the reaction is stirred at room temperature for 72 hours. After the reaction is completed, methanol is added and stirring is continued for 30 min, remove the mixed solvent of methanol and chloroform, then add chloroform to dissolve, remove the chloroform solvent, repeat washing 5 times and vacuum dry to obtain a self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds as shown in structural formula II, wherein in solution C, the ratio of the mixture of 4,4'-diaminodiphenyl disulfide and alcohol hydroxyl-terminated dimethylsiloxane to chloroform is 0.01 mole:500 ml, and the molar ratio of 4,4'-diaminodiphenyl disulfide to alcohol hydroxyl-terminated dimethylsiloxane is 1:0.2; in solution D, the ratio of isophorone diisocyanate to chloroform is 0.01 mole:50 ml; the total molar ratio of 4,4'-diaminodiphenyl disulfide and alcohol hydroxyl-terminated dimethylsiloxane to isophorone diisocyanate is 1:1.

[0063] Furthermore, the preparation method of the self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds shown in the structural formula III comprises the following steps: adding chloroform and 4,4'-diaminodiphenyl disulfide to a four-necked flask equipped with a stirrer, a condenser, a dropping funnel and nitrogen protection, stirring under nitrogen protection to form a uniform solution E, stirring solution E at 0°C for 40 minutes, dissolving diphenylmethane diisocyanate in anhydrous chloroform solution, stirring under nitrogen protection to form a uniform solution F, and then adding solution F dropwise to solution E under nitrogen gas protection and stirring conditions, and after the addition is completed, slowly raising the temperature of the mixed solution to room temperature, and evaporating at room temperature. The mixture was stirred at room temperature for 72 hours, and methanol was added after the reaction was completed and the stirring was continued for 30 minutes. After removing the mixed solvent of methanol and chloroform, chloroform was added to dissolve it, and the chloroform solvent was removed. The mixture was washed 5 times and then vacuum dried to obtain a self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds as shown in structural formula III, wherein in solution E, the ratio of 4,4'-diaminodiphenyl disulfide to chloroform was 0.01 mole:500 ml, and in solution F, the ratio of diphenylmethane diisocyanate to chloroform was 0.01 mole:50 ml, and the molar ratio of 4,4'-diaminodiphenyl disulfide to diphenylmethane diisocyanate was 1:1.

[0064] In the above steps of preparing structural formula I, structural formula II and structural formula III, the volume ratio of the methanol to the chloroform used in the reaction system is 1.2:8.

[0065] Furthermore, the epoxy resin includes bisphenol A epoxy resin, bisphenol F epoxy resin and TDE-85 epoxy resin in a mass ratio of 100:70:50.

[0066] Furthermore, the curing agent is a combination of micron-sized dicyandiamide, micron-sized 4,4-diaminophenyl sulfone and imidazole compounds. The particle sizes of micron-sized dicyandiamide and micron-sized 4,4-diaminophenyl sulfone are both in the range of 5 to 10 microns, and the mass ratio of micron-sized dicyandiamide to micron-sized 4,4-diaminophenyl sulfone is 100:50; the molar ratio of -NH groups to epoxy groups in the curing agent is 1:1.2. The amount of the imidazole compound is 5% of the total mass of the epoxy resin.

[0067] Furthermore, the toughening agent comprises hydroxylated polysulfone resin, carboxyl nitrile rubber functionalized epoxy resin and polyetherimide powder in a mass ratio of 100:50:30, and the toughening agent accounts for 10% of the total mass of the epoxy resin; the particle size of the polyetherimide powder is 25 microns.

[0068] Furthermore, the particle size of the silver nanoparticles in the silver nanoparticle-loaded graphene nanosheets is 10nm-50nm, the loading amount of the silver nanoparticles is 50%, and the amount of the silver nanoparticle-loaded graphene nanosheets is 10% of the total mass of the epoxy resin.

[0069] Furthermore, the mass per unit area of ​​the metal-plated carbon fiber non-woven fabric is 50 g / ㎡, the plated metal is nickel, and the surface resistance is 2.5 Ω / sq.

[0070] Furthermore, the interlayer toughened self-repairing electromagnetic shielding composite material is obtained by hot melt blending, grinding dispersion, vacuum kneading, hot pressing compounding, layer-by-layer cross-stacked and thermal curing, and the specific steps are as follows:

[0071] (1) Preparation of hot melt blends

[0072] The hydroxylated polysulfone resin and the bisphenol A epoxy resin are mixed uniformly, melted and stirred in a hot melt reactor until the thermoplastic hydroxylated polysulfone resin is completely melted in the bisphenol A epoxy resin, and then the mixture is kept warm and stirred for 30 minutes to form a uniform and transparent hot melt blend A, wherein the temperature of the hot melt blend A is maintained at 200°C.

[0073] (2) Preparation of grinding dispersion resin

[0074] First, silver nanoparticle-loaded graphene nanosheets and bisphenol F epoxy resin were ground on a three-roll mill for 5 times to obtain a dispersion resin B, and then the dispersion resin B was mixed with a curing agent and polyetherimide and ground on a three-roll mill for 5 times to obtain a ground dispersion resin C.

[0075] (3) Preparation of blended resin

[0076] The hot melt blend A was preheated to 80°C in a blast drying oven, and the vacuum kneader was set to 50°C for 5 hours. The preheated hot melt blend A, grinding dispersion resin C, carboxyl nitrile rubber functionalized epoxy resin and TDE-85 epoxy resin were added to the preheated vacuum kneader and vacuum kneaded for 15 minutes to obtain blended resin D. During the kneading process, the material temperature was controlled at 60°C and the vacuum degree was controlled at -0.095MPa.

[0077] (4) Preparation of interlayer toughened self-repairing electromagnetic shielding composite materials

[0078] The blended resin D and the metal-plated carbon fiber non-woven fabric are prepared into an electromagnetic shielding prepreg by a hot melt coating machine, and the content of the blended resin D is controlled at 45%. The electromagnetic shielding prepreg and the self-repairing thermoplastic polymer non-woven fabric are cross-laid together and then thermally cured to obtain an interlayer toughened self-repairing electromagnetic shielding composite material. Among them, the self-repairing thermoplastic polymer non-woven fabric is between the electromagnetic shielding prepregs, the curing temperature is 180°C, the curing time is 4h, and the curing pressure is 0.6MPa.

[0079] The interlayer toughened self-repairing electromagnetic shielding composite material prepared by the above steps has the advantages of high electromagnetic shielding efficiency and multiple efficient self-repair between layers. Its electromagnetic shielding effectiveness in the X-band reaches 62dB, and the interlayer repair efficiency is 91%.

[0080] Example 3

[0081] A method for preparing an interlayer toughened self-repairing electromagnetic shielding composite material, wherein the interlayer toughened self-repairing electromagnetic shielding composite material comprises epoxy resin, a curing agent, a toughening agent, silver nanoparticle-loaded graphene nanosheets, a self-repairing thermoplastic polymer non-woven fabric, and a metal-plated carbon fiber non-woven fabric. The interlayer toughened self-repairing electromagnetic shielding composite material is obtained by hot-melt blending, grinding and dispersing, vacuum kneading, hot pressing compounding, layer-by-layer cross-stacking and thermal curing.

[0082] The self-healing thermoplastic polymer non-woven fabric is prepared from a blend of a self-healing thermoplastic elastomer shown in structural formula I, a self-healing thermoplastic elastomer shown in structural formula II, a self-healing thermoplastic elastomer shown in structural formula III, ethylene-methacrylic acid copolymer and ethylene-methyl methacrylate copolymer, wherein the mass ratio of the self-healing thermoplastic elastomer shown in structural formula I, the self-healing thermoplastic elastomer shown in structural formula II, the self-healing thermoplastic elastomer shown in structural formula III, ethylene-methacrylic acid copolymer and ethylene-methyl methacrylate copolymer is 25:90:7.5:75:40; the mass per unit area of ​​the self-healing thermoplastic polymer non-woven fabric is 15 g / m2.

[0083] Furthermore, the self-healing thermoplastic elastomer is a thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds, and the thermoplastic elastomers represented by structural formula I, structural formula II and structural formula III are as follows:

[0084]

[0085]

[0086] The value of n is 3.

[0087] Furthermore, the preparation method of the self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds shown in the structural formula I comprises the following steps: adding chloroform and bis(4-hydroxyphenyl) disulfide to a four-necked flask equipped with a stirrer, a condenser, a dropping funnel and nitrogen protection, stirring under nitrogen protection to form a uniform solution A, stirring solution A at 0°C for 30 minutes, dissolving isophorone diisocyanate and diphenylmethane diisocyanate in anhydrous chloroform solution, stirring under nitrogen protection to form a uniform solution B, and then adding solution B dropwise into solution A under nitrogen gas protection and stirring conditions. After the addition is completed, the temperature of the mixed solution is slowly raised to room temperature, and the reaction is stirred at room temperature for 48 hours. The reaction result is After the mixture was dried, methanol was added and stirring was continued for 22 minutes. After removing the mixed solvent of methanol and chloroform, chloroform was added to dissolve it, and then the chloroform solvent was removed. The mixture was washed four times and then vacuum dried to obtain a self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds as shown in structural formula I, wherein in solution A, the ratio of bis(4-hydroxyphenyl) disulfide to chloroform was 0.01 mole:350 ml, in solution B, the ratio of the mixture of isophorone diisocyanate and diphenylmethane diisocyanate to chloroform was 0.01 mole:35 ml, the molar ratio of isophorone diisocyanate to diphenylmethane diisocyanate was 1:0.3, and the molar ratio of bis(4-hydroxyphenyl) disulfide to diisocyanate was 1:1.

[0088] Furthermore, the preparation method of the self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds shown in the structural formula II comprises the following steps: adding a mixture of 4,4'-diaminodiphenyl disulfide and alcohol hydroxyl-terminated dimethylsiloxane and chloroform to a four-necked flask equipped with a stirrer, a condenser, a dropping funnel and nitrogen protection, stirring under nitrogen protection to form a uniform solution C, stirring solution C at 0°C for 30 minutes, dissolving isophorone diisocyanate in anhydrous chloroform solution, stirring under nitrogen protection to form a uniform solution D, and then adding solution D dropwise to solution C under nitrogen gas protection and stirring conditions. After the addition is completed, the temperature of the mixed solution is slowly raised to room temperature, and the reaction is stirred at room temperature for 48 hours. After the reaction is completed, methanol is added and stirring is continued for 22 min, remove the mixed solvent of methanol and chloroform, then add chloroform to dissolve, remove the chloroform solvent, repeat washing 4 times and vacuum dry to obtain a self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds as shown in structural formula II, wherein in solution C, the ratio of the mixture of 4,4'-diaminodiphenyl disulfide and alcohol hydroxyl-terminated dimethylsiloxane to chloroform is 0.01 mole:350 ml, and the molar ratio of 4,4'-diaminodiphenyl disulfide to alcohol hydroxyl-terminated dimethylsiloxane is 1:0.15; in solution D, the ratio of isophorone diisocyanate to chloroform is 0.01 mole:35 ml; the total molar ratio of 4,4'-diaminodiphenyl disulfide and alcohol hydroxyl-terminated dimethylsiloxane to isophorone diisocyanate is 1:1.

[0089] Furthermore, the preparation method of the self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds shown in the structural formula III comprises the following steps: adding chloroform and 4,4'-diaminodiphenyl disulfide to a four-necked flask equipped with a stirrer, a condenser, a dropping funnel and nitrogen protection, stirring under nitrogen protection to form a uniform solution E, stirring solution E at 0°C for 30 minutes, dissolving diphenylmethane diisocyanate in anhydrous chloroform solution, stirring under nitrogen protection to form a uniform solution F, and then adding solution F dropwise to solution E under nitrogen gas protection and stirring conditions, and after the addition is completed, slowly raising the temperature of the mixed solution to room temperature, and evaporating at room temperature. The mixture was stirred and reacted at room temperature for 48 hours. After the reaction was completed, methanol was added and stirring was continued for 22 minutes. After removing the mixed solvent of methanol and chloroform, chloroform was added to dissolve it, and then the chloroform solvent was removed. The mixture was washed four times and then vacuum dried to obtain a self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds as shown in structural formula III, wherein in solution E, the ratio of 4,4'-diaminodiphenyl disulfide to chloroform was 0.01 mole:350 ml, in solution F, the ratio of diphenylmethane diisocyanate to chloroform was 0.01 mole:35 ml, and the molar ratio of 4,4'-diaminodiphenyl disulfide to diphenylmethane diisocyanate was 1:1.

[0090] In the above steps of preparing structural formula I, structural formula II and structural formula III, the volume ratio of the methanol to the chloroform used in the reaction system is 1.1:8.

[0091] Furthermore, the epoxy resin includes bisphenol A epoxy resin, bisphenol F epoxy resin and TDE-85 epoxy resin in a mass ratio of 100:60:40.

[0092] Furthermore, the curing agent is a combination of micron-sized dicyandiamide, micron-sized 4,4-diaminophenyl sulfone and imidazole compounds. The particle sizes of micron-sized dicyandiamide and micron-sized 4,4-diaminophenyl sulfone are both in the range of 5 to 10 microns, and the mass ratio of micron-sized dicyandiamide to micron-sized 4,4-diaminophenyl sulfone is 100:35; the molar ratio of -NH groups to epoxy groups in the curing agent is 1:1.1; and the amount of the imidazole compound is 3% of the total mass of the epoxy resin.

[0093] Furthermore, the toughening agent comprises hydroxylated polysulfone resin, carboxyl nitrile rubber functionalized epoxy resin and polyetherimide powder in a mass ratio of 100:40:20, and the toughening agent accounts for 7.5% of the total mass of the epoxy resin; the particle size of the polyetherimide powder is 17 microns.

[0094] Furthermore, the particle size of the silver nanoparticles in the silver nanoparticle-loaded graphene nanosheets is 10nm-50nm, the loading amount of the silver nanoparticles is 40%, and the amount of the silver nanoparticle-loaded graphene nanosheets is 6.5% of the total mass of the epoxy resin.

[0095] Furthermore, the mass per unit area of ​​the metal-plated carbon fiber non-woven fabric is 22.5 g / ㎡, the plated metal is a silver-nickel alloy, the mass ratio of silver to nickel is 100:50, and the surface resistance is 1.5Ω / sq.

[0096] Furthermore, the interlayer toughened self-repairing electromagnetic shielding composite material is obtained by hot melt blending, grinding dispersion, vacuum kneading, hot pressing compounding, layer-by-layer cross-stacked and thermal curing, and the specific steps are as follows:

[0097] (1) Preparation of hot melt blends

[0098] The hydroxylated polysulfone resin and the bisphenol A epoxy resin are uniformly mixed, melted and stirred in a hot melt reactor until the thermoplastic hydroxylated polysulfone resin is completely melted in the bisphenol A epoxy resin, and then the mixture is kept warm and stirred for 20 minutes to form a uniform and transparent hot melt blend A. The temperature of the blend is maintained at 190°C.

[0099] (2) Preparation of grinding dispersion resin

[0100] First, silver nanoparticle-loaded graphene nanosheets and bisphenol F epoxy resin were ground on a three-roll mill for 4 times to obtain a dispersion resin B, and then the dispersion resin B was mixed with a curing agent and polyetherimide and ground on a three-roll mill for 4 times to obtain a ground dispersion resin C.

[0101] (3) Preparation of blended resin

[0102] The hot melt blend A was preheated to 65°C in a blast drying oven, and the vacuum kneader was set to 45°C for 4 hours. The preheated hot melt blend A, grinding dispersion resin C, carboxyl nitrile rubber functionalized epoxy resin and TDE-85 epoxy resin were added to the preheated vacuum kneader and vacuum kneaded for 10 minutes to obtain blended resin D. During the kneading process, the material temperature was controlled at 55°C and the vacuum degree was controlled at -0.0965MPa.

[0103] (4) Preparation of interlayer toughened self-repairing electromagnetic shielding composite materials

[0104] The blended resin D and the metal-plated carbon fiber non-woven fabric are prepared into an electromagnetic shielding prepreg by a hot melt coating machine, and the content of the blended resin D is controlled at 42.5%. The electromagnetic shielding prepreg and the self-repairing thermoplastic polymer non-woven fabric are cross-laid together and then thermally cured to obtain an interlayer toughened self-repairing electromagnetic shielding composite material. Among them, the self-repairing thermoplastic polymer non-woven fabric is between the electromagnetic shielding prepregs, the curing temperature is 150°C, the curing time is 3h, and the curing pressure is 0.45MPa.

[0105] The interlayer toughened self-repairing electromagnetic shielding composite material prepared by the above steps has the advantages of high electromagnetic shielding efficiency and multiple efficient self-repair between layers. Its electromagnetic shielding effectiveness in the X-band reaches 65dB, and the interlayer repair efficiency is 92%.

[0106] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A self-healing thermoplastic elastomer containing dynamic covalent bonds, characterized in that: The self-healing thermoplastic elastomer containing dynamic covalent bonds is a thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds. The thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds includes a thermoplastic elastomer shown in structural formula I, structural formula II or structural formula III: The value of n is 2 to 4.

2. The self-healing thermoplastic elastomer containing dynamic covalent bonds according to claim 1, characterized in that: The preparation method of the self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds shown in the structural formula I comprises the following steps: adding chloroform and bis(4-hydroxyphenyl) disulfide to a four-necked flask equipped with a stirrer, a condenser, a dropping funnel and nitrogen protection, stirring under nitrogen protection to form a uniform solution A, keeping the temperature of solution A at 0°C, dissolving isophorone diisocyanate and diphenylmethane diisocyanate in anhydrous chloroform solution, stirring under nitrogen protection to form a uniform solution B, and then dropping solution B dropwise into solution A under nitrogen gas protection and stirring conditions, after the dropping is completed, slowly raising the temperature of the mixed solution to room temperature, stirring and reacting at room temperature for 24 to 72 hours, adding methanol after the reaction is completed and continuing to stir for 1 hour, 5 to 30 minutes, after removing the mixed solvent of methanol and chloroform, chloroform is added again to dissolve, and the chloroform solvent is removed again. The washing is repeated 3 to 5 times and then vacuum dried to obtain a self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds as shown in structural formula I, wherein in solution A, the ratio of bis(4-hydroxyphenyl) disulfide to chloroform is 0.01 mole:200 to 500 ml, in solution B, the ratio of the mixture of isophorone diisocyanate and diphenylmethane diisocyanate to chloroform is 0.01 mole:20 to 50 ml, the molar ratio of isophorone diisocyanate to diphenylmethane diisocyanate is 1:0.2 to 0.4, and the molar ratio of bis(4-hydroxyphenyl) disulfide to diisocyanate is 1:

1.

3. The self-healing thermoplastic elastomer containing dynamic covalent bonds according to claim 1, characterized in that: The preparation method of the self-repairing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds shown in the structural formula II comprises the following steps: A mixture of 4,4'-diaminodiphenyl disulfide and alcohol hydroxyl-terminated dimethylsiloxane and chloroform were added to a four-necked flask equipped with a stirrer, a condenser, a dropping funnel and nitrogen protection. The mixture was stirred under nitrogen protection to form a uniform solution C. The temperature of solution C was kept at 0°C. Isophorone diisocyanate was dissolved in anhydrous chloroform solution. The mixture was stirred under nitrogen protection to form a uniform solution D. Then, solution D was added dropwise to solution C under nitrogen protection and stirring conditions. After the addition was completed, the temperature of the mixed solution was slowly raised to room temperature. The mixture was stirred at room temperature for 24 to 72 hours. After the reaction was completed, methanol was added and stirring was continued for 15 to 30 minutes. After removing the mixed solvent of methanol and chloroform, chloroform was added to dissolve the mixture. The chloroform was removed again. The self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds shown in the structural formula II is obtained after repeated washing 3 to 5 times and vacuum drying, wherein in solution C, the ratio of the mixture of 4,4'-diaminodiphenyl disulfide and alcohol hydroxyl-terminated dimethylsiloxane to chloroform is 0.01 mole:200-500 ml, and the molar ratio of 4,4'-diaminodiphenyl disulfide to alcohol hydroxyl-terminated dimethylsiloxane is 1:0.1-0.2; in solution D, the ratio of isophorone diisocyanate to chloroform is 0.01 mole:20-50 ml; the total molar ratio of 4,4'-diaminodiphenyl disulfide and alcohol hydroxyl-terminated dimethylsiloxane to isophorone diisocyanate is 1:

1.

4. The self-healing thermoplastic elastomer containing dynamic covalent bonds according to claim 1, characterized in that: The preparation method of the self-repairing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds shown in the structural formula III comprises the following steps: Chloroform and 4,4'-diaminodiphenyl disulfide were added to a four-necked flask equipped with a stirrer, a condenser, a dropping funnel and nitrogen protection, and stirred under nitrogen protection to form a uniform solution E. The temperature of solution E was kept at 0°C. Diphenylmethane diisocyanate was dissolved in anhydrous chloroform solution, and stirred under nitrogen protection to form a uniform solution F. Then, solution F was added dropwise to solution E under nitrogen protection and stirring conditions. After the addition was completed, the temperature of the mixed solution was slowly raised to room temperature, and the reaction was stirred at room temperature for 24 to 72 hours. After the reaction was completed, methanol was added and stirring was continued for 15 to 30 minutes. in, removing the mixed solvent of methanol and chloroform and then adding chloroform to dissolve, then removing the chloroform solvent, repeating the washing for 3 to 5 times and vacuum drying to obtain a self-healing thermoplastic elastomer containing dynamic disulfide bonds and dynamic hydrogen bonds as shown in structural formula III, wherein in solution E, the ratio of 4,4'-diaminodiphenyl disulfide to chloroform is 0.01 mole:200 to 500 ml, in solution F, the ratio of diphenylmethane diisocyanate to chloroform is 0.01 mole:20 to 50 ml, and the molar ratio of 4,4'-diaminodiphenyl disulfide to diphenylmethane diisocyanate is 1:

1.

5. The self-repairing thermoplastic elastomer containing dynamic covalent bonds according to claim 2, 3 or 4, characterized in that: The volume ratio of the methanol to the chloroform used in the reaction system is 1-1.2:

8.

6. A method for preparing an interlayer toughened self-repairing electromagnetic shielding composite material, characterized in that: The interlayer toughened self-repairing electromagnetic shielding composite material includes epoxy resin, curing agent, toughening agent, silver nanoparticle-loaded graphene nanosheets, self-repairing thermoplastic polymer non-woven fabric, and metal-plated carbon fiber non-woven fabric. The interlayer toughened self-repairing electromagnetic shielding composite material is obtained by hot melt blending, grinding dispersion, vacuum kneading, hot pressing compounding, layer-by-layer cross-stacking and thermal curing. The self-repairing thermoplastic polymer non-woven fabric is prepared from a blend of a self-repairing thermoplastic elastomer shown in structural formula I, a self-repairing thermoplastic elastomer shown in structural formula II, a self-repairing thermoplastic elastomer shown in structural formula III, ethylene-methacrylic acid copolymer and ethylene-methyl methacrylate copolymer. The mass ratio of the self-repairing thermoplastic elastomer shown in structural formula I, the self-repairing thermoplastic elastomer shown in structural formula II, the self-repairing thermoplastic elastomer shown in structural formula III, ethylene-methacrylic acid copolymer and ethylene-methyl methacrylate copolymer is 20-30:80-100:5-10:50-100:30-50.

7. The preparation method according to claim 6, characterized in that: The self-repairing thermoplastic polymer non-woven fabric has a unit area mass of 10 g / ㎡ to 20 g / ㎡.

8. The preparation method according to claim 6, characterized in that: The epoxy resin comprises bisphenol A epoxy resin, bisphenol F epoxy resin and TDE-85 epoxy resin, and the mass ratio is 100:50-70:30-50. The curing agent is a combination of micron-grade dicyandiamide, micron-grade 4,4-diaminophenyl sulfone and imidazole compounds. The particle sizes of the micron-grade dicyandiamide and micron-grade 4,4-diaminophenyl sulfone are both in the range of 5-10 microns. The mass ratio of the micron-grade dicyandiamide and the micron-grade 4,4-diaminophenyl sulfone is 100:20-50. The amount of the imidazole compound is 1%-5% of the total mass of the epoxy resin. The molar ratio of -NH groups to epoxy groups in the curing agent is 1:1-1.

2.

9. The preparation method according to claim 6, characterized in that: The toughening agent comprises hydroxylated polysulfone resin, carboxyl nitrile rubber functionalized epoxy resin and polyetherimide powder, the mass ratio of which is 100:30-50:10-30, the toughening agent accounts for 5%-10% of the total mass of the epoxy resin, and the particle size of the polyetherimide powder is 10-25 microns; the particle size of the silver nanoparticles in the silver nanoparticle-loaded graphene nanosheets is 10nm-50nm, the loading amount of the silver nanoparticles is 30%-50%, and the amount of the silver nanoparticle-loaded graphene nanosheets is 3%-10% of the total mass of the epoxy resin; the unit area mass of the metal-plated carbon fiber non-woven fabric is 5g / ㎡-50g / ㎡, the plated metal is one of silver, nickel or silver-nickel alloy, and the surface resistance is 0.5-2.5Ω / sq.

10. The preparation method according to claim 9, characterized in that: The interlayer toughened self-repairing electromagnetic shielding composite material is obtained by hot melt blending, grinding dispersion, vacuum kneading, hot pressing compounding, layer-by-layer cross-stacked and thermal curing, and the specific steps are as follows: (1) Preparation of hot melt blends The hydroxylated polysulfone resin and the bisphenol A epoxy resin are uniformly mixed, melted and stirred in a hot melt reactor until the thermoplastic hydroxylated polysulfone resin is completely melted in the bisphenol A epoxy resin, and then the mixture is kept warm and stirred for 10 to 30 minutes to form a uniform and transparent hot melt blend A, wherein the temperature of the blend is maintained at 180 to 200° C.; (2) Preparation of grinding dispersion resin Firstly, silver nanoparticle-loaded graphene nanosheets and bisphenol F epoxy resin are ground on a three-roll mill for 3 to 5 times to obtain a dispersion resin B, and then the dispersion resin B is mixed with a curing agent and polyetherimide and ground on a three-roll mill for 3 to 5 times to obtain a ground dispersion resin C; (3) Preparation of blended resin The hot melt blend A is preheated to 50-80° C. in a blast drying oven, the heating temperature of the vacuum kneader is set to 40-50° C., and the preheating is performed for 3-5 hours. The preheated hot melt blend A, the grinding and dispersion resin C, the carboxyl nitrile rubber functionalized epoxy resin and the TDE-85 epoxy resin are added to the preheated vacuum kneader, and the blended resin D is obtained by vacuum kneading for 5-15 minutes; wherein, the material temperature is controlled at 50-60° C., and the vacuum degree is controlled at -0.098MPa to -0.095MPa during the kneading process; (4) Preparation of interlayer toughened self-repairing electromagnetic shielding composite materials The blended resin D and the metal-coated carbon fiber non-woven fabric are prepared into an electromagnetic shielding prepreg by a hot melt coater, and the content of the blended resin D is controlled at 40% to 45%. The electromagnetic shielding prepreg and the self-repairing thermoplastic polymer non-woven fabric are cross-laid together and then thermally cured to obtain an interlayer toughened self-repairing electromagnetic shielding composite material, wherein the self-repairing thermoplastic polymer non-woven fabric is between the electromagnetic shielding prepregs, the curing temperature is 120 to 180°C, the curing time is 2 to 4 hours, and the curing pressure is 0.3 to 0.6 MPa.